Pemanfaatan Twitter Buzzer Untuk Meningkatkan Partisipasi Pemilih Muda dalam Pemilihan Umum - Yuliahsari, Dwi (Jurnal The Messenger, 2015)
This article tries to describe the use of twitter buzzer as one way to increase the participation of young voters in the general election in Indonesia. The theoretical basis of this paper is the theory of diffusion - innovation that illustrates the power of mass media messages in influencing attitudes and behavior as well as spread the new discovery. Through the use of descriptive qualitative methods can be drawn that social media twitter with all its advantages and supported by the buzzer as an opinion leader, then the use of twitter buzzer become one of the solutions to increase the participation of young voters in the general election in Indonesia. But its utility must be adapted to the characteristics of the audience, so that appropriate goals and objectives are achieved with the maximum.